Present and future heat stress of preschoolers in five Swedish cities - Nils Wallenberg; David Rayner; Fredrik Lindberg; Sofia Thorsson (Climate Risk Management, 2023)
Heat stress can have negative effects on human wellbeing with morbidity and mortality as harmful consequences, especially in vulnerable groups, e.g. children, elderly and chronically ill. Children is for example at higher risk of dehydration and heat stroke compared to healthy adults. Furthermore, children attending preschools are endorsed to spend time outdoors and engaging in physical activities. Therefore, thermally comfortable preschool yards are detrimental to sustain safe environments where the children can continue their physically active play. Here we show that preschoolers in five Swedish cities, Malmö, Gothenburg, Stockholm, Östersund and Luleå, are exposed to heat stress on warm and clear days between May-August in preschool yards with insufficient shading, using three different thermal indices (COMFA, PET and UTCI). Furthermore, future number of heat stress days are evaluated using the SMHI RCA4 regional climate model from the EURO-CORDEX project, forced with six different global climate models. Results show that heat stress will increase under the RCP2.6, 4.5 and 8.5 climate change scenarios. In Malmö, Gothenburg and Stockholm number of days with heat stress all hours 09:00–15:00 while playing in a sunlit sandbox have doubled from approximately 10 to 20 days for 2071–2100 (RCP8.5) compared to 2008–2020. These numbers are even higher if active play, e.g. running, is performed, estimating to around two weeks in July alone by the end of the century. Without adaptation this is likely to have adverse effects on the health and learning of children. If the preschool yard, on the other hand, is shaded by trees, days with heat stress are almost entirely diminished, indicating the importance of trees in preschool yard design as a tool to mitigate heat stress.